Medicinal Plants : Their Role in Health and Biodiversity - Akerele, Olayiwola; Tomlinson, Timothy R. (Book collections on Project MUSE., 1998)
From the beginning of human civilization, people have depended on plants to cure disease, promote healing of injuries, and alleviate pain. In many places that has changed very little. In the West, however, herbal and botanical cures have long been ignored in favor of "scientific medicine." But the benefits of medicinal plants are being rediscovered in many developed countries, where consumers are turning to such therapies in place of, and in addition to, Western medical treatments. And, all over the world, the drive to lower the cost of health care has made herbals and botanicals an attractive alternative to more expensive synthetic remedies. In 1978, the World Health Organization responded to increased interest in medicinal plants by convening a series of international consultations, seminars, and symposia to explore and promote the use of medicinal plants. Medicinal Plants presents the proceedings of the last of these symposia, held in 1993. It brings together an vast range of information and presents an overview of the use of medicinal plants that includes a discussion of a variety of issues--scientific, economic, regulatory, agricultural, cultural--focused on the importance of medicinal plants to primary health care and global health care reform